Retraction: Correlation of Serum Uric Acid Levels with The Severity Of Coronary Artery Stenosis in Patients with Acute CoronarySyndrome: Meta-Analysis Study - Prasetyo, Diding Heri; Nasution, Sally Aman; Alwi, Idrus; Abdullah, Murdani (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. The relationship between serum uric acid (SUA) level and ischemic heart disease abides controversial and still has not been established as a cardiovascular risk factor. The cooperative interaction between those two factors is not fully understood. Prior epidemiological evidences of the causal relationship is still argumentative. There were various studies using the same methods yet the outcome were different. This study aims to conduct a meta-analysis to synthesize the results of recent studies in order to obtain data quantitatively and also accurately. Methods. This study protocol was registered with PROSPERO (CRD42020210948), and conducted according to PRISMA guidelines, tracing studies published in vulnerable periods from January 2010 to May 2020. The Cochrane Library, EBSCO, Medline/PubMed, ProQuest and Science Direct are sources of published studies. Meta-analysis was conducted to synthesize the associations between SUA level and severity of coronary artery stenosis, using random effect model to account for possible study heterogeneity. Heterogeneity was assessed using I2 , and the meta-analysis was performed using comprehensive meta-analysis version 3 (CMA3) software. Results. Five studies (n = 601 patients) identified a correlation between serum uric acid levels and Gensini scores (r = 0.548; p <0.001) in ACS patients. Heterogeneity bias was found in the analysis, whereas publication bias was not found. There was a moderate positive correlation between serum uric acid levels and the severity of coronary artery stenosis, with a correlation coefficient of 0.548 (p value <0.001).